2020
DOI: 10.3389/fphar.2020.00643
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbiomes in Pregnant Women and Offspring: Research Progress of Recent Years

Abstract: Pregnancy is a complicated and delicate process, the maternal body undergoes changes on hormones, immunity, and metabolism during pregnancy to support fetal development. Microbiomes in the human body mainly live in the intestine, and the human gut microbiomes are complex, which composed of more than 500 to 1500 different bacteria, archaea, fungi, and viruses. Studies have shown that these microbiomes are not only involved in the digestion and absorption of food but also indispensable in regulating host health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 125 publications
0
32
0
2
Order By: Relevance
“…Studies indicated that the reconstitution of VLDLR expression in macrophages of VLDLR-deficient mice promotes the occurrence and development of atherosclerosis, which may be due to the accumulation of atherosclerotic lipoproteins caused by the knockout of VLDLR (124,125). The physical state of the mother has a profound impact on the health of the fetus (126,127). Maternal-fetal interface studies suggest that VLDLR can induce osteoclasts differentiation and inhibit the inflammatory response of macrophages (128)(129)(130).…”
Section: Maternal Vldlrmentioning
confidence: 99%
“…Studies indicated that the reconstitution of VLDLR expression in macrophages of VLDLR-deficient mice promotes the occurrence and development of atherosclerosis, which may be due to the accumulation of atherosclerotic lipoproteins caused by the knockout of VLDLR (124,125). The physical state of the mother has a profound impact on the health of the fetus (126,127). Maternal-fetal interface studies suggest that VLDLR can induce osteoclasts differentiation and inhibit the inflammatory response of macrophages (128)(129)(130).…”
Section: Maternal Vldlrmentioning
confidence: 99%
“…However, that hypothesis assumes that the maternal gut or vaginal microbiome that the fetus was exposed to was healthy. Whether the microbiome effects are dependent on maternal health status and the state the gut microbiome warrants further exploration (Koren et al, 2012; Yao et al, 2020).…”
Section: Maternal Microbiome: Implications On Offspring Healthmentioning
confidence: 99%
“…RA is common among women, and the ratio of men to women is close to 1:3. In women with RA, it seems to be more difficult to conceive, and the disease activity affects the mother and fetal outcome (Wallenius et al, 2011;Wallenius et al, 2012;Yao et al, 2020). For example, RA patients have a longer time to pregnancy (TTP).…”
Section: The Treatment Of Rheumatoid Arthritis During Pregnancy and Lmentioning
confidence: 99%